Comparison of short-term clinical outcomes between transanal and laparoscopic total mesorectal excision for the treatment of mid and low rectal cancer: A meta-analysis. Issue 12 (December 2016) - Xu, W.; Xu, Z.; Cheng, H.; Ying, J.; Cheng, F.; Xu, W.; Cao, J.; Luo, J.
Abstract: Aim: The objective of this meta-analysis was to evaluate the feasibility, safety, and short-term clinical outcomes of transanal total mesorectal excision (TaTME) comparing with laparoscopy total mesorectal excision (LapTME) for mid and low rectal cancer. Methods: Relevant studies were searched from the databases of Pubmed, Embase, and the Cochrane Library. The qualities of all of the included studies were evaluated using Newcastle–Ottawa Scale (NOS). The synthesized outcomes were pooled using fixed-effects models or random-effects models, which weighted the odds ratio (OR) or mean difference (MD) with 95% confidence intervals (95% CI). A funnel plot was used to evaluate the publication bias. Results: Seven original studies including 209 TaTME patients and 257 LapTME patients with rectal cancer met the inclusion criteria in this meta-analysis. Compared with LapTME, TaTME showed a longer CRM, lower rate of positive CRM, complete TME rate, and less operative time. There were no significant differences in the outcomes of the harvested lymph nodes, distal margin distance, hospital stay, intraoperative complications, anastomotic leakage, postoperative complications, reoperation, readmission, or conversion between the TaTME group and the LapTME group. Conclusions: Compared with LapTME, TaTME is a feasible and safe approach for patients with mid and low rectal cancer. In addition, TaTME showed a better short-term clinical outcomes, such as a longer CRM, lower risk of positive CRM, higher complete quality of TME rate, and shorter operative duration. Further prospective studies with long-term follow-up are required.